2003
DOI: 10.1016/s0735-1097(02)02718-3
|View full text |Cite
|
Sign up to set email alerts
|

Raised serum levels of soluble CD40 ligand in patients with familial hypercholesterolemia: downregulatory effect of statin therapy

Abstract: Our findings may suggest enhanced CD40L-CD40 interaction in FH and that this inflammatory response may be downregulated by statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 29 publications
6
68
2
3
Order By: Relevance
“…[16][17][18][19] There is evidence that the sCD40L level is a strong predictor of cardiovascular risk. 20 In literature, enhanced levels of CD40L were reported in patients with hypercholesterolemia, [21][22][23] diabetes mellitus, 24,25 and acute coronary syndromes. [26][27][28][29] Few studies have reported the relationship between obesity and sCD40L.…”
Section: Soluble Cd40 Ligand and C-reactive Proteinmentioning
confidence: 99%
“…[16][17][18][19] There is evidence that the sCD40L level is a strong predictor of cardiovascular risk. 20 In literature, enhanced levels of CD40L were reported in patients with hypercholesterolemia, [21][22][23] diabetes mellitus, 24,25 and acute coronary syndromes. [26][27][28][29] Few studies have reported the relationship between obesity and sCD40L.…”
Section: Soluble Cd40 Ligand and C-reactive Proteinmentioning
confidence: 99%
“…25 Statin treatment significantly reduces CD40 and CD40L expression and lowers sCD40L in patients with familial hypercholesterolemia. 70 Blockade of CD40L by neutralizing antibodies or genetic disruption of CD40L in mice appears to prevent the initiation and progression of atherosclerosis and induces a more stable plaque with fewer inflammatory cells, less lipids, and more smooth muscle cells and collagen. 71,72 Elevated levels of soluble and membranebound forms of CD40L have been reported for patients with angina, 73 after cardiopulmonary bypass surgery, 74 and with congestive heart failure.…”
Section: Cd40/cd40l Interactionsmentioning
confidence: 99%
“…In a study of patients with stable coronary syndromes or strong family history of cardiovascular disease, both conventional and more aggressive statin therapy decreased sCD40L over 2 years, with greater lowering at 2 years than at 1 year. 19 In addition to the fact that different patients were studied (those with stable coronary syndromes), in that study, sCD40L was measured from serum after the blood samples were allowed to clot. 19 sCD40L concentrations tend to be higher in serum (reflecting greater release from platelets activated by clot formation) than in EDTA plasma such as was used in the present study.…”
Section: Effect Of Statin Therapymentioning
confidence: 99%
“…15,18 Two studies in patients with stable coronary syndromes also indicate that statins may reduce sCD40L. 18,19 However, the impact of statins on sCD40L in patients with acute coronary syndromes has not been studied prospectively in a large randomized, controlled trial.…”
mentioning
confidence: 99%